Taylor Dome Ice Core Chemistry, Ion, and Isotope Data - Indermuhle, A.; Brook, Edward J.; Smith, Jesse; Sowers, Todd A.; Mayewski, Paul A.; Steig, Eric J. (IEDA: US Antarctic Program Data Center, 2004)
This data set includes chemistry, ion, and istotope data from Taylor Dome, part of the East Antarctic ice sheet. Deep drilling at Taylor Dome successfully reached bedrock at a depth of 554 meters during the 1993-1994 austral summer. The Taylor Dome ice core is only the second core (after Vostok) to provide a stratigraphically undisturbed record through the entire last glacial cycle (the last 130,000 years or more).